A New Era of HIV Risk It's Not What You Know, It's Who You Know (and How Infectious). [article]. - Cortopassi, Andrew C.
HIV is transmitted in social and sexual relationships, and HIV transmission risks, as well as protective actions, are evolving as HIV epidemics unfold. The current focus of HIV prevention is centered on antiretroviral medications used to reduce HIV infectiousness in persons already infected with HIV [treatment as prevention (TasP)]. The same medications used to treat infected persons can also be used by uninfected persons as pre-exposure prophylaxis (PrEP) to reduce the infectivity of HIV. Both PrEP and TasP are effective when adherence is high and individuals do not have co-occurring sexually transmitted infections. HIV prevention is most effective and efficient when delivered within sexual networks with high HIV prevalence. Specific network characteristics are recognized as important facilitators of HIV transmission; these characteristics include the degree of similarity among network members (homophily), gender role norms, and belief systems. Since 2011, HIV risk has been redefined based on infectiousness and infectivity, ushering in a new era of HIV prevention with the potential to end HIV epidemics. -- (from the author)